Mahmud al-kashgari's divanü lügati't-türk i-ii-iii (2024). azerbaijan national academy of sciences, nasimi institute of linguistics, baku: azerbaijan - Uzun, Cemile (Ahmet BURAN, 2024)
Divanu Lügati't Türk (DLT), written by Kashgarli Mahmud in the XI century, has been translated and printed into various languages and Turkic dialects over time. Khalid Said Khojayev is one of the important researchers working on DLT. The first translation of DLT from Arabic to Latin letters belongs to Khalid Said. Khalid Said's translation is important in terms of being the first translation of DLT in Latin script both in Azerbaijan Turkic and in the Turkic world. Khalid Said started the translation of the work in 1935 and finished the translation in 1936, but could not publish the work. The translation of DLT in Azerbaijani language was unearthed after 86 years. With the decision of the Presidium of the Azerbaijan National Academy of Sciences dated 29 January 2024, Nesimi was prepared for publication by the Institute of Linguistics. This study includes the introduction of the work published by the Presidium of the Azerbaijan National Academy of Sciences. In the study, the features of Khalid Said's translation of DLT, the edition and structure of the work were emphasised.

XI. yy.da Kaşgarlı Mahmud tarafından kaleme alınan Divanu Lügati’t Türk’ün (DLT) çeşitli dillere ve Türk lehçelerine zaman içerisinde çevirisi ve baskısı yapılmıştır. Halid Said Hocayev de DLT üzerinde çalışan önemli araştırmacılardan biridir. DLT’nin Arap harflerinden Latin harflerine ilk tercümesi Halid Said’e aittir. Halid Said’in tercümesi hem Azerbaycan Türkçesinde hem de Türk dünyasında DLT’nin Latin harfli ilk tercümesi olması bakımından önemlidir. Halid Said, 1935 yılında başladığı eserin tercümesini 1936’da bitirmiş; ancak tercümeyi yayınlayamamıştır. DLT’nin Azerbaycan dilindeki tercümesi 86 yıl sonra gün yüzüne çıkarılmıştır. Azerbaycan Ulusal Bilimler Akademisi Başkanlık Heyeti’nin 29 Ocak 2024 tarihli kararı ile Nesimi Dil Bilim Enstitüsü tarafından yayıma hazırlanmıştır. Bu çalışma, Azerbaycan Ulusal Bilimler Akademisi Başkanlık Heyeti tarafından yayımlanan eserin tanıtımını içermektedir. Çalışmada, Halid Said’in DLT tercümesinin özellikleri, eserin baskısı ve yapısı üzerinde durulmuşur.
MAHMUD KAŞĞARİ DİVANÜ LÜGAT-İT-TÜRK I-II-III (2024). AZ?RBAYCAN MİLLİ ELML?R AKADEMİYASI N?SİMİ ADINA DİLÇİLİK İNSTİTUTU, BAKI: AZERBAYCAN
Keywords: Old Turkic Language (Orhon; Uyghur; Karahan); Eski Türk Dili (Orhun; Uygur; Karahanlı)